Assessment of Effective Communication Competencies Possessed by University Business Education Graduates for Successful Running of Businesses in South South Nigeria (Global Journal of Management and Business Research, 2013)
This study investigated employers assessment of effective communication competencies possessed by uni- versity Business Education graduates for successful running of businesses in south south Nigeria. One research question and three hypotheses guided the study. The study adopted descriptive survey design. The population comprised 318 employers of Business Education graduates in Rivers State and Delta State. The population also served as sample since it was manageable. The instrument for data collection was a 20 item questionnaire whose face and content were adequately validated by experts. The instrument internal consistency was determined using cronbach alpha, which has reliability of 0.93. The research question data were analyzed using mean and standard deviation. Z-test was used to test the hypotheses at 0.05 level of significance. The finding of the study revealed among others that Business Education graduates are competent in ability to speak clearly with empathy, ability to display good listening skills, ability to interpret message correctly, ability to relate information appropriately to concerned parties. However, they are not competent in ability to formulate points of view and ability to meet the functional needs of the media. It was recommended among others that university Business Education graduates should constantly undergo training and retaining on communication courses to be more competent in all communication skills, more business communication courses should be built in business education curriculum to enable the students acquire more com-munication competencies.
Keywords: assessment; communication competencies; university business education graduates; south south nigeria